Analisis Laporan Keuangan Toko DJ Aksesoris Bengkulu Menurut SAK ETAP Guna Menilai Kelayakan Pembiayaan - Adela Putri; Vivi Oktari (Journal of Innovative and Creativity, 2025)
This research analyzes the financial statements of DJ Accessories Store in Bengkulu according to Standards of Financial Accounting for Entities Without Public Accountability (SAK ETAP) to assess financing feasibility. DJ Accessories Store is classified as a small business that has implemented SAK ETAP since 2024 following government-sponsored training programs. The study employs a qualitative descriptive approach using observation, interviews, and documentation techniques to examine how the store's accounting practices align with SAK ETAP standards. The financial statements analyzed include balance sheets, income statements, statements of changes in equity, cash flow statements, and notes to financial statements for the fiscal year ending December 31, 2024. Findings indicate that the store has successfully implemented most SAK ETAP components, demonstrating a healthy financial condition with net income of Rp 563,170,000. However, the cash flow statement remains incomplete as it lacks detailed information on investing and financing activities. The store's financial position shows strong liquidity and solvency ratios, meeting banking standards for credit financing. Principal constraints identified include limited accounting expertise among personnel and fragmented recording systems requiring further optimization. The research concludes that despite minor deficiencies, DJ Accessories Store's financial statements meet criteria for financing eligibility, though continued support for human resource development and integrated accounting systems is essential for sustainable improvement and future business development.